2013
DOI: 10.1038/cddis.2013.95
|View full text |Cite
|
Sign up to set email alerts
|

GSK-3β signaling determines autophagy activation in the breast tumor cell line MCF7 and inclusion formation in the non-tumor cell line MCF10A in response to proteasome inhibition

Abstract: The ubiquitin–proteasome system and the autophagy–lysosome pathway are the two main mechanisms for eukaryotic intracellular protein degradation. Proteasome inhibitors are used for the treatment of some types of cancer, whereas autophagy seems to have a dual role in tumor cell survival and death. However, the relationship between both pathways has not been extensively studied in tumor cells. We have investigated both proteolytic systems in the human epithelial breast non-tumor cell line MCF10A and in the human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 50 publications
(69 reference statements)
4
37
0
Order By: Relevance
“…Autophagy is the degradation of unnecessary or dysfunctional cellular components through the formation of autophagosomes to ensure cellular survival during starvation by maintaining cellular energy levels. Several previous reports show evidence of contrasting effects of GSK-3 in regulating autophagy (4248). Here we have shown that GSK-3 inhibition induced autophagy as evident from increased LC3B levels in the renal cancer cells upon GSK-3 inhibition.…”
Section: Discussionmentioning
confidence: 95%
“…Autophagy is the degradation of unnecessary or dysfunctional cellular components through the formation of autophagosomes to ensure cellular survival during starvation by maintaining cellular energy levels. Several previous reports show evidence of contrasting effects of GSK-3 in regulating autophagy (4248). Here we have shown that GSK-3 inhibition induced autophagy as evident from increased LC3B levels in the renal cancer cells upon GSK-3 inhibition.…”
Section: Discussionmentioning
confidence: 95%
“…Besides, GSK3␤, as a direct downstream target of Akt, is implicated in several signaling pathways and then regulates expression of many genes. Gavilán et al recently reported that Akt/GSK3␤ signaling pathway determined autophagy activation in tumor cell [42]. Indeed, GSK3␤ negatively regulated autophagy, and elevated GSK3␤ phosphorylation at Ser9 simulated autophagy activation and promoted the expression of autophagy-related proteins, such as LC3II and beclin1 [42][43][44][45].…”
Section: Discussionmentioning
confidence: 98%
“…Gavilán et al recently reported that Akt/GSK3␤ signaling pathway determined autophagy activation in tumor cell [42]. Indeed, GSK3␤ negatively regulated autophagy, and elevated GSK3␤ phosphorylation at Ser9 simulated autophagy activation and promoted the expression of autophagy-related proteins, such as LC3II and beclin1 [42][43][44][45]. Parr et al reported that GSK3␤ inhibition promoted lysosomal biogenesis and autophagic degradation of A␤PP [45].…”
Section: Discussionmentioning
confidence: 99%
“…If GSK3␤ inhibition in preconditioned hearts promotes lysosomal biogenesis, this may hypothetically prime the cell for enhanced autophagic glycogen disposal. Similarly GSK3␤ has been shown to regulate autophagic activity in both tumor and nontumor cell lines (18). Fig.…”
Section: Mitochondrial Clearance (Mitophagy) and Mitochondrial Sequesmentioning
confidence: 99%